The effect of air pollution on the risk of inflammatory bowel disease, colorectal cancer and appendicitis - Król, Dominika; Sak, Justyna; Mazurkiewicz, Wojciech; Nowiński, Michał; Fus-Mazurkiewicz, Laura (Journal of Education, Health and Sport, 2024)
Introduction and objective Intense industrial development is contributing to increased emissions of air pollutants. Numerous studies indicate a link between air pollution and a higher risk of pulmonary and cardiovascular diseases. Our goal is to analyze available scientific studies to demonstrate the relationship between air pollution and the risk of developing and complicating inflammatory bowel disease, colorectal cancer and appendicitis. Brief description of the state of knowledge Air pollution is a global health challenge. Particles such as PM, nitrogen oxides, sulfur oxides or ozone have a significant impact on health. Studies suggest a link between pollution and intestinal diseases (IBD, CRC, appendicitis). Air pollutants can affect the gut by causing inflammation, oxidative stress and disruption of the gut microbiota. Exposure to PM2.5 can increase the risk of IBD, CRC, and PM10 can increase the risk of UC. There is a correlation between pollution and the rate of hospitalization for IBD. In addition, exposure to PM2.5 increases the risk of colorectal cancer mortality. Short-term exposure to air pollution is associated with more hospitalizations for appendicitis. Summary Air pollution is a real health risk. Reducing air pollution could potentially reduce the risk of developing these intestinal diseases and their complications. Despite the potential links, further research is required to better understand the mechanisms of action of pollutants on intestinal health. Urgent and coordinated global and local action is needed to reduce air pollution emissions and protect the health of the public.